2016
DOI: 10.1590/2317-1782/20162015256
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre a percepção da posição de língua pelo indivíduo e medidas de força da língua nos dentes

Abstract: No significant difference was found between the tongue forces of participants of both groups at habitual position. However, participants with tongue thrust during directed swallowing presented greater force than those whose tongues do not touch the teeth during this task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The aim of this pilot and preliminary study is to assess separately postural stability in different tongue conditions and cervical ROM in healthy subjects in order to find out any relationships. The tongue position is a postural characteristic and depends from several aspects (Gonzalez et al, 2019;Valentim et al, 2016). To investigate its effects on postural oscillations is fundamental in terms of postural assessment and treatment (Vuillerme et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this pilot and preliminary study is to assess separately postural stability in different tongue conditions and cervical ROM in healthy subjects in order to find out any relationships. The tongue position is a postural characteristic and depends from several aspects (Gonzalez et al, 2019;Valentim et al, 2016). To investigate its effects on postural oscillations is fundamental in terms of postural assessment and treatment (Vuillerme et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…They also reported other effects of altered tongue proprioception, showing difficulties recognizing the tongue position, which could result in dysarthria for some patients [ 18 ]. Other studies have observed relationships between tongue force and tongue position [ 25 ] and between tongue force exercises and subjective perception of fatigue [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The position of the tongue and lips at rest has been investigated over the years in individuals of different age groups (7)(8)(9)(10)(11)(12) with the aim of verifying its impact on the orofacial development. However, only one study was carried out with babies (13) .…”
Section: Introductionmentioning
confidence: 99%